PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE HARGA POKOK PESANAN PADA CV MITRA BISNIS ANDA - Zidna Farihah Hayat; Sulistiyo - (Politeknik Negeri Semarang, 2019)
The aim of this research to identify the elements of cost of production and calculate the cost of production of CV Mitra Bisnis Anda with the Cost of Job Order Method. Writing method used is descriptive and exposition method. Meanwhile, the exposition describes the classification of costs according to the method of job order and calculation of the cost of production for each product. The method of analysis used is comparative analysis, that is by comparing the calculation of cost of production by the job order method with the cost of production by the company. Based on the calculation and analysis that has been done, there is a difference in cost of production amounted to Rp. 33.137,53.-, for the springbedsandaran kotak is Rp. 22.864,13.-, while for the springbedsandaran konde isRp. 10.273,4.-. The difference arises because there are differences in the classification of production costs, the company does not include depreciation cost because the company has not shrunk its assets, nor does not include the cost of repairs and maintenance when calculating the factory overhead costs